The Dysferlin Transcript Containing the Alternative Exon 40a is Essential for Myocyte Functions - Ballouhey, Océane; Courrier, Sébastien; Kergourlay, Virginie; Gorokhova, Svetlana; Cerino, Mathieu; Krahn, Martin; Lévy, Nicolas; Bartoli, Marc (Frontiers in Cell and Developmental Biology, 2021)
Dysferlinopathies are a group of muscular dystrophies caused by recessive mutations in the DYSF gene encoding the dysferlin protein. Dysferlin is a transmembrane protein involved in several muscle functions like T-tubule maintenance and membrane repair. In 2009, a study showed the existence of fourteen dysferlin transcripts generated from alternative splicing. We were interested in dysferlin transcripts containing the exon 40a, and among them the transcript 11 which contains all the canonical exons and exon 40a. This alternative exon encodes a protein region that is cleaved by calpains during the muscle membrane repair mechanism. Firstly, we tested the impact of mutations in exon 40a on its cleavability by calpains. We showed that the peptide encoded by the exon 40a domain is resistant to mutations and that calpains cleaved dysferlin in the first part of DYSF exon 40a. To further explore the implication of this transcript in cell functions, we performed membrane repair, osmotic shock, and transferrin assay. Our results indicated that dysferlin transcript 11 is a key factor in the membrane repair process. Moreover, dysferlin transcript 11 participates in other cell functions such as membrane protection and vesicle trafficking. These results support the need to restore the dysferlin transcript containing the alternative exon 40a in patients affected with dysferlinopathy.